2019
DOI: 10.1038/s41598-019-49718-5
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal and vertical integrative analysis methods for mental disorders omics data

Abstract: In recent biomedical studies, omics profiling has been extensively conducted on various types of mental disorders. In most of the existing analyses, a single type of mental disorder and a single type of omics measurement are analyzed. In the study of other complex diseases, integrative analysis, both vertical and horizontal integration, has been conducted and shown to bring significantly new insights into disease etiology, progression, biomarkers, and treatment. In this article, we showcase the applicability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Significantly different from the existing studies, a new analysis strategy is proposed to borrow information across a GeO‐GGM and its corresponding GeR‐GGM, so that the estimation of the GeO‐GGM can assist the estimation of the GeR‐GGM, and vice versa. Loosely speaking, this strategy shares some similar spirit with the vertical data integration (Wang et al, 2019). This study may advance from the existing literature in the following aspects.…”
Section: Introductionmentioning
confidence: 91%
“…Significantly different from the existing studies, a new analysis strategy is proposed to borrow information across a GeO‐GGM and its corresponding GeR‐GGM, so that the estimation of the GeO‐GGM can assist the estimation of the GeR‐GGM, and vice versa. Loosely speaking, this strategy shares some similar spirit with the vertical data integration (Wang et al, 2019). This study may advance from the existing literature in the following aspects.…”
Section: Introductionmentioning
confidence: 91%
“…Transfer learning has been applied to problems in medical and biological studies, including predictions of protein localization (Mei et al, 2011), biological imaging diagnosis (Shin et al, 2016), drug sensitivity prediction (Turki et al, 2017) and integrative analysis of 'multi-omics' data, see, for instance, Sun and Hu (2016), Hu et al (2019), and Wang et al (2019). It has also been applied to natural language processing (Daumé III, 2007) and recommendation systems (Pan & Yang, 2013) in machine learning.…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that, through the combination of different types of omics data, scientists can better capture or dissect the genetic contribution in a specific disease. Some successful applications include several breast cancer studies ( Beckmann et al, 2007 ; Curtis et al, 2012 ; Zahnleiter et al, 2013 ; Hendrickx et al, 2017 ), a prostate cancer study ( Taylor et al, 2010 ), and a study of mental disorders ( Wang et al, 2019 ). Review articles about such integrated analysis have received great attention recently (see for instance Richardson et al, 2016 ; Sun and Hu, 2016 ; and Wu et al, 2019 , among many others and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative, methods that examine simultaneously both types of markers have been adopted. Such a scheme is termed as hierarchical or vertical ( Richardson et al, 2016 ; Wang et al, 2019 ; Wu et al, 2019 ). For instance, Gamazon et al (2014) suggested the use of a single SNV association test with the copy number status as a covariate to achieve better performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation